The Role of Interleukin-8 in Lung Inflammation and Injury: Implications for the Management of COVID-19 and Hyperinflammatory Acute Respiratory Distress Syndrome - Cesta, Maria Candida; Zippoli, Mara; Marsiglia, Carolina; Gavioli, Elizabeth Marie; Mantelli, Flavio; Allegretti, Marcello; Balk, Robert A. (Frontiers in Pharmacology, 2022)
Severe Acute Respiratory Syndrome Coronavirus – 2 (SARS CoV-2) has resulted in the global spread of Coronavirus Disease 2019 (COVID-19) and an increase in complications including Acute Respiratory Distress Syndrome (ARDS). Due to the lack of therapeutic options for ARDS, recent attention has focused on differentiating hyper- and hypo-inflammatory phenotypes of ARDS to help define effective therapeutic strategies. Interleukin 8 (IL-8) is a pro-inflammatory cytokine that has a role in neutrophil activation and has been identified within the pathogenesis and progression of this disease. The aim of this review is to highlight the role of IL-8 as a biomarker and prognostic factor in modulating the hyperinflammatory response in ARDS. The crucial role of IL-8 in lung inflammation and disease pathogenesis might suggest IL-8 as a possible new therapeutic target to efficiently modulate the hyperinflammatory response in ARDS.